Comparing bioelectrical activity of the central retina among myopic patients operated for rhegmatogenous retinal detachment complicated by choroidal detachment (Ukrainian Journal of Ophthalmology, 2026)
Background: Rhegmatogenous retinal detachment (RRD) is a serious incapacitating disease requiring surgical treatment. Trophic disturbances in the central and peripheral retina are characteristic for myopia, which is known to be a major risk factor for RRD.Purpose: 1) To investigate the bioelectrical activity of the central retina after successful surgery for combined RRD and CD in patients differing in the degree of myopia, and 2) to compare the characteristics with those of normal eyes and myopic patients successfully operated for uncomplicated RRD.Materials and Methods: Fifty two patients (52 eyes) were included into the study 3 months after undergoing a single successful vitrectomy with gas tamponade, either for uncomplicated RRD (32 eyes), or combined RRD and CD  (20 eyes). They were divided into four groups: Groups 1 and 2 (moderate and high myopes after surgery for uncomplicated RRD; 21 and 11 patients, respectively), and Groups 3 and 4 (moderate and high myopes after surgery for combined RRD and CD; 9 and 11 patients, respectively). Fourteen age-matched individuals (28 eyes) without any ocular or systemic disease were enrolled as controls (Group 5). Photopic cone response and photopic 30 Hz flicker cone response were recorded to examine the bioelectrical activity of the central retina.Results: A-wave and b-wave implicit times of the photopic cone response (a) reflect conductance related to the photoreceptor and inner layers, respectively, of the central retina, and (b) were 25% longer and 28% longer, respectively, for myopic eyes after surgery for either uncomplicated RRD or combined RRD and CD, than for normal eyes. A-wave amplitude of the photopic cone response (a) reflects the summed bioelectrical activity of retinal photoreceptor cones, and (b) in moderately or highly myopic eyes after surgery for uncomplicated RRD was 1.9-fold and 3.5-fold lower, respectively, and in moderately or highly myopic eyes after surgery for combined RRD and CD, 3.9-fold and 6.6-fold lower, respectively, than in normal eyes. B-wave amplitude of the photopic cone response (a) reflects the summed bioelectrical activity of the retinal inner layers, and (b) in moderately or highly myopic eyes after surgery for uncomplicated RRD was 1.6-fold and 2.8-fold lower, respectively, whereas in those after surgery for combined RRD and CD, 3.8-fold lower, than in normal eyes. Amplitude of photopic 30 Hz flicker cone response (a) reflects the bioelectrical activity of cones, and (b) in moderately myopic eyes after surgery for uncomplicated RRD was 1.6-fold lower, whereas in myopic eyes after surgery for combined RRD and CD, 2.8-fold lower, than in normal eyes. We found direct correlations between BCVA and b-wave and a-wave amplitudes of the photopic cone response (r = 0.61 and r = 0.54, respectively), and amplitude of the 30 Hz flicker response (r = 0.53), and an inverse correlation (r=-0.53) between BCVA and a-wave implicit time of the photopic cone response for myopic eyes after surgery for either uncomplicated RRD or combined RRD and CD.Conclusion: Bioelectrical activity of the central retina was found to be more decreased in highly myopic eyes after surgery for  combined RRD and CD than in other myopic eyes of the study.
Keywords: rhegmatogenous retinal detachment; choroidal detachment; electroretinography